"Stuck in their Ways": Examining Parole Officers’ Perceptions on Guiding Older Offenders through the Reentry Process - Hughes, Mary H. (American journal of criminal justice, 2022)
Parole officers serve a critical role for inmates who are reentering society by monitoring the transitional and rehabilitation process post incarceration. Recently, there has been increased concern among correctional professionals in regard to addressing economic and management barriers of aging inmates. Elderly offenders require unique resources with regard to their health and housing and parole officers represent the initial contact for this population when providing the assistance; however, little is known about the role parole officers play in the reintegration process for older inmates. Therefore, the current study examined the perceptions of 19 parole officers who work with older parolees in a southern state. Through semi-structured, qualitative interviews, we explored parole officers’ primary role in the reintegration process to gain better understanding of demographics, management, and established goals when assisting older parolees.